Hasan Langgulung Thought on Islamic Education - Musyafaah, Nurul; Manshur, Ahmad; Sufi Maisyaroh, Afina; Syaikhu Rohman, Khabib; Afthon Ulin Nuha, Muhammad (TSAQAFAH, 2023)
Hasan Langgulung is a thinker who is quite influential and has contributed significantly to the development of Islamic education in Indonesia and outside Indonesia. He is one of the thinkers of contemporary Islamic education, where he has contributed ideas that have been contained in several books that are thick with the study of Islamic education. Langulung thought has an exciting style and characteristic to study, especially about the development of Islamic education felt, by reviewing several aspects of its field of expertise, namely education, psychology, language, history, and philosophy. The purpose of this study 1) To determine the concept of Islamic education thought according to Hasan Langgulung. 2) To determine the implementation of Hasan Langgulung's Islamic educational thought in Indonesia. This study uses a qualitative approach. Data collection was done by interview, observation and documentation. Data analysis was done through data reduction, data presentation and conclusion drawing. The results of this study indicate that 1) the thought of Islamic education, according to Langgulung, emphasises the word at-trading, namely, educating humans. The education process should pay attention to the basics of humanity, consider students intelligent creatures of God, and have the right to receive an education. Respect, love and guidance. 2) According to Hasan Langgulung, the Islamization of science must be carried out due to several factors that cannot be avoided, first, the current globalisation, which emphasises science and technology; second, the science of the Qur'an explains a lot about science; this is efforts to prove that all knowledge comes from the Qur'an and hadith.